Pelatihan Digital Marketing Bagi UMKM Dalam Meningkatkan Daya Saing di Era Digital - Saleh, Saleh; Zulkifli, Zulkifli; Pratama Putra, Dani; Izwar, Akmal (LPPM Umuslim, 2024)
The training focuses on introducing and implementing effective digital marketing strategies, such as social media marketing, search engine optimization, online advertising, and online reputation management. The methods used include workshops and direct mentoring for SMEs. The results of the activity show a significant increase in participants' understanding of digital marketing strategies, as well as an increased awareness of the importance of digital marketing in improving business competitiveness in the digital age. Additionally, this activity successfully facilitated the formation of a communication network among SMEs, serving as a platform for sharing information and experiences related to utilizing digital marketing strategies. Through this initiative, it is expected that SMEs in Gampong Beurawang will be better prepared to face business competition in the digital era, thereby increasing their income and well-being